Amelioration of clinical course and demyelination in the cuprizone mouse model in relation to ketogenic diet. Issue 6 (15th June 2020) - Zhang, Ning; Liu, Chunhong; Zhang, Ruiyan; Jin, Li; Yin, Xiaohan; Zheng, Xuexing; Siebert, Hans-Christian; Li, Yubao; Wang, Zhengping; Loers, Gabriele; Petridis, Athanasios K.
Abstract : Ketogenic diet (KD) is defined as a high-fat, low-carbohydrate diet with appropriate amounts of protein, which has broad neuroprotective effects. Abstract : Ketogenic diet (KD) is defined as a high-fat, low-carbohydrate diet with appropriate amounts of protein, which has broad neuroprotective effects. However, the mechanisms of ameliorating the demyelination and of the neuroprotective effects of KD have not yet been completely elucidated. Therefore, the present study investigated the protection mechanism of KD treatment in the cuprizone (bis-cyclohexanone oxalydihydrazone, CPZ)-induced demyelination mice model, with special emphasis on neuroinflammation. After the KD treatment, an increased ketone body level in the blood of mice was detected, and a significant increase in the distance traveled within the central area was observed in the open field test, which reflected the increased exploration and decreased anxiety of mice that received CPZ. The results of Luxol fast blue and myelin basic protein (MBP) immunohistochemistry staining for the evaluation of the myelin content within the corpus callosum revealed a noticeable increase in the number of myelinated fibers and myelin score after KD administration in these animals. Concomitant, the protein expressions of glial fibrillary acidic protein (GFAP, an astrocyte marker), ionized calcium-binding adaptor molecule 1 (Iba-1, a microglial marker), CD68 (an activated microglia marker) and CD16/32 (a M1 microglial marker) were down-regulated, while the expression of oligodendrocyte lineage transcription factor 2 (OLIG2, an oligodendrocyte precursor cells marker) was up-regulated by the KD treatment. In addition, the KD treatment not only reduced the level of the C–X–C motif chemokine 10 (CXCL10), which is correlated to the recruitment of activated microglia, but also inhibited the production of proinflammatory cytokines, including interleukin 1β (IL-1β) and tumor necrosis factor-α (TNF-α), which are closely correlated to the M1 phenotype microglia. It is noteworthy, that the expression levels of histone deacetylase 3 (HADC3) and nod-like receptor pyrin domain containing 3 (NLRP3) significantly decreased after KD administration. In conclusion, these data demonstrate that KD decreased the reactive astrocytes and activated the microglia in the corpus callosum, and that KD inhibited the HADC3 and NLRP3 inflammasome signaling pathway in CPZ-treated mice. This suggests that the inhibition of the HADC3 and NLRP3 signaling pathway may be a novel mechanism by which KD exerts its protective actions for the treatment of demyelinating diseases.